Temperature constraints by Raman spectroscopy of organic matter in volatile-rich clasts and carbonaceous chondrites. (15th November 2018) - Visser, Robbin; John, Timm; Menneken, Martina; Patzek, Markus; Bischoff, Addi
Abstract: An important question regarding the formation of the solar system is how planetary bodies developed from dust and ice into the planets and planetary bodies. A particularly interesting topic is the thermal evolution of carbonaceous chondrites and volatile-rich clasts that could have originated from CM- and CI-like parent bodies. Two types of these volatile-rich clasts, which are a particular type of dark clasts, can be found. These clasts are mineralogically very similar to CM and CI chondrites and can occasionally be found in achondritic meteorites. Mineral assemblages suggest that both CM and CI chondrites as well as volatile-rich clasts experienced low peak temperatures. However, these mineral assemblages only offer large estimated temperature ranges to describe the thermal history of CM and CI chondrites, and the thermal history of volatile-rich clasts has not been previously described. In this study, to gain a better understanding of the thermal history of both CM and CI chondrites and volatile-rich clasts, we estimated peak temperatures of 30 volatile-rich clasts (16 CI-, and 14 CM-like) in 10 different host meteorites (4 polymict ureilites, 5 polymict eucrites and 1 howardite) by Raman carbon thermometry. An automated method was developed in order to describe over 4000 collected Raman spectra using four pseudovoigt functions. The full width half maximum (FWHM) of the D1-band was then used to calculate peak temperatures. Results were then compared to Raman data of 8 different well-studied carbonaceous chondrites (including CI and CM chondrites) to evaluate the suggestion that volatile-rich clasts are composed of similar material to the equivalent CI and CM chondrites. Our results show that the peak temperatures experienced by CI-like clasts range between 30–110 °C with an average of about 65 ± 25 °C; the peak temperatures experienced by CM-like clasts range from 50 to 110 °C with an average of about 70 ± 25 °C. Six of the 8 studied carbonaceous chondrites (CM, CI, CR or C2ungr ) also plot in the same low-temperature range between 50 °C and 75 °C and can thus be considered to have formed under similar temperature conditions as the volatile-rich clasts. This is in agreement with previous suggestions, based on their mineral compositions that volatile-rich clasts and CI and CM carbonaceous chondrites are composed of similar materials. The peak temperatures for carbonaceous chondrites determined in this study considerably reduce the range of temperature estimates proposed previously for these chondrites by different methods. By highlighting the ability of our methodology to evaluate data in an automated way, this study shows that Raman carbon thermometry is a good analytical technique for obtaining information about peak temperatures in small and delicate samples.